Inhibition of Glial Activation in Rostral Ventromedial Medulla Attenuates Mechanical Allodynia in a Rat Model of Cancer-induced Bone Pain - 刘希江 卜慧莲 刘成 高峰 杨辉 田学愎 许爱军 陈治军 曹菲 田玉科 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
Descending nociceptive modulation from the supraspinal structures plays an important role in cancer-induced bone pain (CIBP). Rostral ventromedial medulla (RVM) is a critical compo-nent of descending nociceptive facilitation circuitry, but so far the mechanisms are poorly known. In this study, we investigated the role of RVM glial activation in the descending nociceptive facilitation circuitry in a CIBP rat model. CIBP rats showed significant activation of microglia and astrocytes, and also up-regulation of phosphorylated p38 mitogen-activated protein kinase (p38 MAPK) and pro-inflammatory mediators released by glial cells (IL-1β, IL-6, TNF-α and brain-derived neurotro-phic factor) in the RVM. Stereotaxic microinjection of the glial inhibitors (minocycline and ?uorocitrate) into CIBP rats' RVM could reverse the glial activation and significantly attenuate me-chanical allodynia in a time-dependent manner. RVM microinjection of p38 MAPK inhibitor (SB203580) abolished the activation of microglia, reversed the associated up-regulation of pro-inflammatory mediators and significantly attenuated mechanical allodynia. Taken together, these results suggest that RVM glial activation is involved in the pathogenesis of CIBP. RVM microglial p38 MAPK signaling pathway is activated and leads to the release of downstream pro-inflammatory mediators, which contribute to the descending facilitation of CIBP.